A toughening agent for strengthening the impact resistance of prepreg

By using a toughening agent made of a mixture of oil and aqueous phase, combining carbon fiber with resin matrix to form a composite system, the problems of insufficient impact resistance and interlayer toughness of existing carbon fiber reinforced composite materials in high temperature and high humidity environments are solved. A significant performance improvement has been achieved.

CN115850890BActive Publication Date: 2025-02-25JIANGSU ZHONGFU SHENYING CARBON FIBER ENG CENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211507548.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2025-02-25
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

The impact resistance and interlayer toughness of existing carbon fiber reinforced composite materials in high temperature and high humidity environments are insufficient, making it difficult to meet the needs of high-end applications such as aerospace.

Method used

A toughening agent made of oil-phase mixture and aqueous-phase mixture is used to form a toughening agent with uniform particle size and controllable particle size through emulsification reaction, and a composite system is formed by combining carbon fibers and resin matrix to improve the impact resistance and layer of the prepreg Interstitial toughness.

Benefits of technology

It significantly improves the impact resistance and interlayer toughness of carbon fiber reinforced composite materials, and is suitable for high-end applications such as aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115850890B_ABST
    Figure CN115850890B_ABST
Patent Text Reader

Abstract

The present application provides a toughening agent, a preparation method thereof and its application. The toughening agent provided in the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture and the aqueous phase mixture is 1:0.7 to 1:1.8; the oil phase mixture includes thermoplastics and organic solvents; the aqueous phase mixture includes polyvinyl alcohol and deionized water; the mass percentage of each component in the oil phase mixture is expressed as: thermoplastics 5 to 20%, organic solvents 80 to 95%; the mass percentage of each component in the aqueous phase mixture is expressed as: polyvinyl alcohol 3 to 18%, deionized water 82 to 97%; the organic solvent is a single organic solvent or a composite organic solvent, a single organic solvent includes N-methyl-2-pyrrolidone, and a composite organic solvent includes methanol and chloroform. The impact resistance, interlaminar toughness and other properties of the prepreg and carbon fiber reinforced composite material made of the toughening agent of the present application are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of prepreg production, and in particular to a toughening agent, and a preparation method and application of the toughening agent. Background Art

[0002] Carbon fiber reinforced composite materials are widely used in aircraft structural parts, windmill blades, turbines and other manufacturing fields that need to withstand tensile and compressive stresses due to their excellent strength and impact resistance. The composite material is composed of carbon fiber, toughening material, resin matrix and other main components to improve the tolerance of structural parts in high temperature and high humidity environments and stress impact performance outside the carbon fiber arrangement direction.

[0003] The demand for lightweight, stress resistance and interlayer toughness of composite materials in high-end carbon fiber application fields such as aerospace is becoming increasingly obvious. The prepreg prepared by only using a resin matrix with low toughness and carbon fiber coating has poor performance and poor impact resistance, and has low material toughness and adaptability. At present, the research and development of this material is limited by the high-performance requirements of the back-end application field, the lag of domestic related research, and the poor independent deployment ability. There is no systematic, clear and mature material molding process and preparation method in the domestic related research field. Summary of the invention

[0004] The present application aims to provide a toughening agent, which is a composite system formed by physically dispersing the toughening agent of the present application and a resin matrix, and can be uniformly impregnated between carbon fiber layers, and made into a prepreg through processes such as coating, hot pressing, cooling, laminating, and curling. The impact resistance and interlayer toughness of the prepreg prepared by the prepreg are significantly improved, and it is widely used in high-end carbon fiber application fields such as aerospace.

[0005] In order to achieve the above technical effects, this application adopts the following technical solutions:

[0006] According to one aspect of the present application, a toughening agent is provided, which is made of an oil phase mixture and a water phase mixture; the mass percentage ratio of the oil phase mixture to the water phase mixture is 1:0.7 to 1:1.8.

[0007] Wherein, the oil phase mixture includes thermoplastic plastics and organic solvents; the water phase mixture includes polyvinyl alcohol and deionized water;

[0008] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0009] Thermoplastics 5-20%;

[0010] Organic solvent 80-95%;

[0011] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0012] Polyvinyl alcohol 3-18%;

[0013] Deionized water 82-97%.

[0014] The thermoplastic plastic includes one or more of polyethersulfone, polyurethane, polyamide, polyimide and polycarbonate.

[0015] Wherein, the organic solvent is a single organic solvent or a composite organic solvent.

[0016] Wherein, the single organic solvent comprises N-methyl-2-pyrrolidone;

[0017] The composite organic solvent includes methanol and chloroform; the ratio of the methanol to the chloroform is 1:2.3 to 1:4.1.

[0018] Wherein, if the organic solvent includes the single organic solvent, the mass percentage ratio of the thermoplastic plastic to the single organic solvent is 1:14 to 1:20;

[0019] If the organic solvent includes the composite organic solvent, the mass percentage ratio of the thermoplastic plastic to the composite organic solvent is 1:7.1 to 1:14.3.

[0020] Preferably, the mass percentage of each component in the oil phase mixture is expressed as follows:

[0021] Thermoplastics 7-14%,

[0022] Organic solvent 86-93%;

[0023] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0024] Polyvinyl alcohol 5-10%,

[0025] Deionized water 90-95%;

[0026] Wherein, the organic solvent is a single organic solvent or a composite organic solvent;

[0027] If the organic solvent includes the single organic solvent, the mass percentage ratio of the thermoplastic to the single organic solvent is 1:14 to 1:18;

[0028] If the organic solvent includes the composite organic solvent, the mass percentage ratio of the thermoplastic plastic to the composite organic solvent is 1:8.5 to 1:12.5.

[0029] The toughening agent of the present application is made by emulsification reaction of a water phase mixture and an oil phase mixture, and the two phases are mixed. Thermoplastic plastic is a macromolecular polymer, which is the main component of the toughening agent and constitutes the matrix of the toughening agent; the organic solvent is used as the dispersed phase of the thermoplastic plastic to open, disperse and dissolve the thermoplastic plastic; polyvinyl alcohol is a surfactant, and its molecular chain includes hydrophilic groups and lipophilic groups, and its lipophilic group is combined with the surface of the thermoplastic plastic in the oil phase, and the hydrophilic group at the other end is exposed to the water phase, so that the thermoplastic plastic macromolecules reach a mutually exclusive state during the emulsification reaction, thereby achieving the purpose of maintaining the particle size of the toughening agent stable and uniform and preventing it from agglomerating. Therefore, the toughening agent of the present application has the advantages of uniform, controllable, stable particle size, and high sphericity. The carbon fiber reinforced composite material prepared using the toughening agent of the present application has high impact resistance, high interlayer toughness, and few product defects.

[0030] The functions and contents of the various components used in the preparation of the toughening agent are described as follows:

[0031] An oil phase mixture and an aqueous phase mixture are used in the preparation process of the toughening agent of the present application; wherein the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.7 to 1:1.8; wherein the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water.

[0032] Thermoplastic plastics are the main components of the toughening agent of the present application and constitute the matrix of the toughening agent. Thermoplastic plastics are thermoplastic, high in hardness and elastic. The prepreg and carbon fiber reinforced composite materials prepared from the toughening agent composed of the thermoplastic plastics and carbon fiber, resin matrix, etc., have significantly improved properties such as impact resistance, tolerance to high temperature and high humidity environments, and interlayer toughness. Preferably, the thermoplastic plastics include one or more of polyether sulfone, polyurethane, polyamide, polyimide and polycarbonate. In the toughening agent of the present application, the thermoplastic plastics are limited to 5 to 20% of the total mass of the oil phase mixture; preferably, the thermoplastic plastics account for 7 to 14% of the total mass of the oil phase mixture.

[0033] The organic solvent is the dispersed phase of the thermoplastic, which can disperse, open and dissolve the thermoplastic. In the toughening agent of the present application, the organic solvent is limited to 80-95% of the total mass of the oil phase mixture; preferably, the organic solvent accounts for 86-93% of the total mass of the oil phase mixture. Preferably, the organic solvent selected in the present application is a single organic solvent or a composite organic solvent. Preferably, the single organic solvent may include N-methyl-2-pyrrolidone, and the composite organic solvent may include chloroform and methanol. When the selected organic solvent is a composite organic solvent, the ratio of chloroform and methanol will affect the dispersion effect of the thermoplastic, so it is necessary to select chloroform and methanol with a suitable ratio to maximize the dispersion, opening and dissolution of the thermoplastic. In the toughening agent of the present application, when the selected organic solvent is a composite organic solvent, the ratio of methanol to chloroform is 1:2.3 to 1:4.1.

[0034] During the research process, it was found that the mass percentage ratio of thermoplastics and organic solvents will affect the dispersion effect of thermoplastics. Therefore, in order to disperse, open and dissolve thermoplastics to the greatest extent without wasting costs, the mass percentage ratio of thermoplastics and organic solvents must be limited to an appropriate range. In the toughening agent of the present application, when the organic solvent includes a single organic solvent, the mass percentage ratio of thermoplastics to the single organic solvent is 1:14 to 1:20; preferably, when the organic solvent includes a single organic solvent, the mass percentage ratio of thermoplastics to the single organic solvent is 1:14 to 1:18. In the toughening agent of the present application, when the organic solvent includes a composite organic solvent, the mass percentage ratio of thermoplastics to the composite organic solvent is 1:7.1 to 1:14.3; preferably, when the organic solvent includes a composite organic solvent, the mass percentage ratio of thermoplastics to the composite organic solvent is 1:8.5 to 1:12.5.

[0035] Polyvinyl alcohol is a surfactant for preparing the toughening agent in the present application. Its molecular chain includes hydrophilic groups and lipophilic groups. When it is dissolved in water to form a polyvinyl alcohol solution, when the polyvinyl alcohol solution is added to the oil phase mixture described in the present application, the lipophilic groups on the polyvinyl alcohol molecular chain are combined with the surface of the thermoplastic plastic in the oil phase, and the hydrophilic groups at the other end are exposed to the water phase, so that the thermoplastic plastic macromolecules reach a mutually exclusive state during the emulsification reaction process of preparing the toughening agent, thereby achieving the purpose of maintaining the toughening agent particle size stable and uniform and preventing it from agglomerating. In the toughening agent of the present application, the polyvinyl alcohol is limited to 3-18% of the total mass of the water phase mixture; preferably, the polyvinyl alcohol accounts for 5-10% of the total mass of the water phase mixture.

[0036] Deionized water is a solvent for polyvinyl alcohol and constitutes the aqueous phase system for preparing the toughening agent by emulsification reaction in the present application. In the toughening agent of the present application, deionized water is limited to 82-97% of the total mass of the aqueous phase mixture; preferably, deionized water accounts for 90-95% of the total mass of the aqueous phase mixture.

[0037] According to a second aspect of the present application, a method for preparing the toughening agent is provided, comprising the following steps:

[0038] S1: placing the organic solvent in a container, heating it to a preset temperature, adding a preset weight of the thermoplastic plastic, dispersing the thermoplastic plastic in the organic solvent, and stirring to obtain a first dispersed system;

[0039] S2: dispersing the mixed solution of the polyvinyl alcohol and the deionized water into the first dispersed system described in S1 to obtain a second dispersed system;

[0040] S3: subjecting the second dispersed system described in S2 to particle size classification, subjecting the sieved intermediate to solid-liquid separation, drying, and pulverization to obtain the toughening agent.

[0041] Among them, between step S1 and step S2, it also includes:

[0042] S4: Fill nitrogen into the container in S1 to replace the gas in the container.

[0043] Preferably, the specific operation of step S2 is: adding and dispersing the mixed solution of polyvinyl alcohol and deionized water into the first dispersed system described in S1 at a rate of 0.20 to 0.35 kg / min, stirring until the system presents a uniform milky white emulsion, to obtain a second dispersed system.

[0044] According to a third aspect of the present application, there is provided application of the toughening agent in a manufacturing process of prepreg and carbon fiber reinforced composite material.

[0045] In the toughening agent of the present application, the beneficial effects of selecting the above-mentioned range of the content of each component will be explained by giving specific experimental data through examples.

[0046] The following are examples of preferred value ranges for the components included in the toughening agent according to the present application.

[0047] Preferred Example 1

[0048] The toughening agent according to the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.7 to 1:1.8; the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water;

[0049] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0050] Thermoplastics 5-20%;

[0051] Organic solvent 80-95%;

[0052] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0053] Polyvinyl alcohol 3-18%;

[0054] Deionized water 82-97%.

[0055] Preferred Example 2

[0056] The toughening agent according to the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.7 to 1:1.8; the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water;

[0057] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0058] Thermoplastics 5-20%;

[0059] Organic solvent 80-95%;

[0060] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0061] Polyvinyl alcohol 3-18%;

[0062] Deionized water 82-97%;

[0063] The organic solvent is a single organic solvent or a composite organic solvent; if the composite organic solvent includes methanol and chloroform, the ratio of the methanol to the chloroform is 1:2.3 to 1:4.1.

[0064] Preferred Example 3

[0065] The toughening agent according to the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.9 to 1:1.5; the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water;

[0066] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0067] Thermoplastics 5-20%;

[0068] Organic solvent 80-95%;

[0069] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0070] Polyvinyl alcohol 3-18%;

[0071] Deionized water 82-97%;

[0072] The organic solvent is a single organic solvent or a composite organic solvent; if the composite organic solvent includes methanol and chloroform, the ratio of the methanol to the chloroform is 1:2.3 to 1:4.1; if the organic solvent includes the single organic solvent, the mass percentage ratio of the thermoplastic plastic to the single organic solvent is 1:14 to 1:20; if the organic solvent includes the composite organic solvent, the mass percentage ratio of the thermoplastic plastic to the composite organic solvent is 1:7.1 to 1:14.3.

[0073] Preferred Example 4

[0074] The toughening agent according to the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.7 to 1:1.8; the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water;

[0075] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0076] Thermoplastics 7-14%,

[0077] Organic solvent 86-93%;

[0078] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0079] Polyvinyl alcohol 5-10%,

[0080] Deionized water 90-95%.

[0081] Preferred Example 5

[0082] The toughening agent according to the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.7 to 1:1.8; the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water;

[0083] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0084] Thermoplastics 7-14%,

[0085] Organic solvent 86-93%;

[0086] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0087] Polyvinyl alcohol 5-10%,

[0088] Deionized water 90-95%;

[0089] Preferred Example 6

[0090] The toughening agent according to the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.9 to 1:1.5; the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water;

[0091] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0092] Thermoplastics 7-14%,

[0093] Organic solvent 86-93%;

[0094] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0095] Polyvinyl alcohol 5-10%,

[0096] Deionized water 90-95%;

[0097] Wherein, the organic solvent is a single organic solvent or a composite organic solvent; if the organic solvent includes the single organic solvent, the mass percentage ratio of the thermoplastic plastic to the single organic solvent is 1:14 to 1:18; if the organic solvent includes the composite organic solvent, the mass percentage ratio of the thermoplastic plastic to the composite organic solvent is 1:8.5 to 1:12.5.

[0098] Preferred Example 7

[0099] The toughening agent according to the present application is made of an oil phase mixture and an aqueous phase mixture; the mass percentage ratio of the oil phase mixture to the aqueous phase mixture is 1:0.9 to 1:1.5; the oil phase mixture includes thermoplastic plastics and organic solvents, and the aqueous phase mixture includes polyvinyl alcohol and deionized water;

[0100] The mass percentage of each component in the oil phase mixture is expressed as follows:

[0101] Thermoplastics 9-13%,

[0102] Organic solvent 87-91%;

[0103] The mass percentage of each component in the aqueous phase mixture is expressed as follows:

[0104] Polyvinyl alcohol 6-9%,

[0105] Deionized water 91-94%;

[0106] Wherein, the organic solvent is a single organic solvent or a composite organic solvent; if the organic solvent includes the single organic solvent, the mass percentage ratio of the thermoplastic plastic to the single organic solvent is 1:14 to 1:16; if the organic solvent includes the composite organic solvent, the mass percentage ratio of the thermoplastic plastic to the composite organic solvent is 1:9.5 to 1:11.5. BRIEF DESCRIPTION OF THE DRAWINGS

[0107] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0108] Figure 1 This is a scanning electron microscope image of the toughening agent prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0109] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.

[0110] The formula raw materials and preparation methods of the toughening agents of Examples 1 to 10 of the present application are as follows:

[0111] Embodiment 1

[0112] Weigh 63kg of chloroform and 27kg of methanol into a container, heat to 30°C and stir until uniform; then add 11kg of thermoplastic (CXT9413 / Shandong Xianglong New Materials), stir and dissolve to obtain the first dispersion system; weigh 100kg of polyvinyl alcohol solution consisting of 7kg of polyvinyl alcohol and 93kg of deionized water, add it dropwise to the first dispersion system at a rate of 0.3kg / min, stir until the system presents a uniform milky white emulsion, and obtain the second dispersion system; distill the second dispersion system at a vacuum degree of -0.09Mpa for 8h to remove the organic solvent, wash and grade the resulting slurry, perform particle size classification, and rinse and dilute with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Bag, put in a desiccant, and seal and store at room temperature.

[0113] Embodiment 2

[0114] Weigh 30.0kg of N-methyl-2-pyrrolidone and place it in a container, heat it to 30°C and stir it until it is uniform; then add 2kg of thermoplastic (constituent is polyamide), stir and dissolve it to obtain a first dispersion system; fill the container with nitrogen, and replace the gas in the container with 95-99% nitrogen; weigh 43kg of polyvinyl alcohol solution composed of 3kg polyvinyl alcohol and 40kg deionized water, and add it dropwise to the first dispersion system at a speed of 0.3kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.09Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, classify the particle size, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Bag it, put in a desiccant, and seal it at room temperature.

[0115] Embodiment 3

[0116] Weigh 68.4kg of chloroform and 21.6kg of methanol into a container, heat to 30°C and stir until uniform; then add 10kg of thermoplastic (PA12 / MACMI), stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, and replace the gas in the container with 95-99% of nitrogen; weigh 100kg of polyvinyl alcohol solution consisting of 7kg of polyvinyl alcohol and 93kg of deionized water, and add it dropwise to the first dispersion system at a speed of 0.3kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; fill the container with nitrogen, and replace the air in the system with 95-99% of nitrogen; distill the second dispersion system at a vacuum degree of -0.07Mpa for 8h to remove the organic solvent, wash the resulting slurry with water, classify it, perform particle size classification, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing, etc. of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Pack in bags, add desiccant, and seal at room temperature.

[0117] Embodiment 4

[0118] Weigh 70kg of chloroform and 30kg of methanol into a container, heat to 30°C and stir until uniform; then add 7.1kg of thermoplastic (PA11 / BECN P20 TL, ARKEMA), stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, and replace the gas in the container with 95-99% nitrogen; weigh 100kg of polyvinyl alcohol solution consisting of 18kg of polyvinyl alcohol and 82kg of deionized water, and add it dropwise to the first dispersion system at a speed of 0.3kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.08Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, classify the particle size, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Bag it, put in a desiccant, and seal it at room temperature.

[0119] Embodiment 5

[0120] Weigh 80.4kg of chloroform and 20.6kg of methanol into a container, heat to 30°C and stir until uniform; then add 14.0kg of thermoplastic (constituent is polyethersulfone), heat to 78°C, stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, and replace the gas in the container with 95-99% nitrogen; weigh 100kg of polyvinyl alcohol solution consisting of 3kg of polyvinyl alcohol and 97kg of deionized water, and add it dropwise to the first dispersion system at a speed of 0.3kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.06Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, classify the particle size, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Bag it, put in a desiccant, and seal it at room temperature.

[0121] Embodiment 6

[0122] Weigh 24kg of N-methyl-2-pyrrolidone and place it in a container, heat it to 60°C; then add 1.6kg of thermoplastic (constituent is polycarbonate), stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, replace the gas in the container with 95-99% nitrogen, and heat the container to 78°C until the thermoplastic in the container is completely dissolved; weigh 37.8kg of polyvinyl alcohol solution composed of 8.2kg of polyvinyl alcohol and 38.4kg of deionized water, add it dropwise to the first dispersion system at a speed of 0.2kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.09Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, perform particle size classification, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Pack in bags, add desiccant, and seal at room temperature.

[0123] Embodiment 7

[0124] Weigh 71.25kg of chloroform and 23.75kg of methanol into a container and heat to 60°C; then add 9kg of thermoplastic (constituent is polycarbonate), stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, replace the gas in the container with 95-99% of nitrogen, and heat the container to 78°C until the thermoplastic in the container is completely dissolved; weigh 72.8kg of polyvinyl alcohol solution consisting of 2.2kg of polyvinyl alcohol and 70.6kg of deionized water, add it dropwise to the first dispersion system at a speed of 0.2kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.09Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, perform particle size classification, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Pack in bags, add desiccant, and seal at room temperature.

[0125] Embodiment 8

[0126] Weigh 60kg of chloroform and 20kg of methanol and place them in a container, heat to 60°C; then add 10kg of thermoplastic (constituent is polycarbonate), stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, replace the gas in the container with 95-99% nitrogen, and heat the container to 78°C until the thermoplastic in the container is completely dissolved; weigh 162kg of polyvinyl alcohol solution composed of 29.16kg of polyvinyl alcohol and 132.84kg of deionized water, add it dropwise to the first dispersion system at a speed of 0.2kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.09Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, perform particle size classification, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Pack in bags, add desiccant, and seal at room temperature.

[0127] Embodiment 9

[0128] Weigh 95kg of N-methyl-2-pyrrolidone and place it in a container, heat it to 60°C; then add 4.75kg of thermoplastic (constituent is polycarbonate), stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, replace the gas in the container with 95-99% nitrogen, and heat the container to 78°C until the thermoplastic in the container is completely dissolved; weigh 76.8kg of polyvinyl alcohol solution composed of 6.2kg of polyvinyl alcohol and 70.6kg of deionized water, add it dropwise to the first dispersion system at a speed of 0.2kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.09Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, classify it by particle size, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Pack in bags, add desiccant, and seal at room temperature.

[0129] Embodiment 10

[0130] Weigh 96kg of N-methyl-2-pyrrolidone and place it in a container, heat it to 60°C; then add 6.8kg of thermoplastic (constituent is polycarbonate), stir and dissolve to obtain a first dispersion system; fill the container with nitrogen, replace the gas in the container with 95-99% nitrogen, and heat the container to 78°C until the thermoplastic in the container is completely dissolved; weigh 152kg of polyvinyl alcohol solution composed of 24.16kg of polyvinyl alcohol and 127.84kg of deionized water, add it dropwise to the first dispersion system at a speed of 0.2kg / min, stir until the system presents a uniform milky white emulsion, and obtain a second dispersion system; distill the second dispersion system at a vacuum degree of -0.09Mpa for 8h to remove the organic solvent, wash the obtained slurry with water, classify it, perform particle size classification, and rinse and dilute it with 65°C hot water. After solid-liquid separation, drying, crushing and other treatments of the sieved intermediate, a micron-sized powder material, i.e., a toughening agent, is obtained. Pack in bags, add desiccant, and seal at room temperature.

[0131] In order to further illustrate the beneficial effects of the present application, a powder material and a preparation method thereof are provided as a comparative example 1, as shown below:

[0132] Weigh 10 kg of thermoplastic plastic (constituent: polyamide), add the above materials into a liquid nitrogen mill and set the freezing temperature to -50°C, crush the thermoplastic plastic for 4 hours to obtain a fine powder material. After the above fine powder material is subjected to particle size classification and drying treatment, a powder material is obtained.

[0133] The following is a comparison of the product characteristics of the toughening agent of the embodiment of the present invention and the powder material of the comparative example 1 in the form of a table.

[0134] Table 1 Product characteristics test results of the embodiments and comparative examples

[0135]

[0136] The toughening agent provided in this application has a high sphericity, and its sphericity is greater than or equal to 95%. Figure 1 As shown, Figure 1 This is a scanning electron microscope image of the toughening agent prepared in Example 5, and its sphericity reaches 98%. Due to its spherical shape characteristics, when applied to prepreg and carbon fiber reinforced composite materials, it can dilute and buffer impact energy, thereby greatly improving the toughness and impact resistance of the material.

[0137] From Table 1 and Figure 1It can be seen that compared with Comparative Example 1, the toughening agent of the present invention: (i) has a higher sphericity, which can be controlled at 95-100%; (ii) has a diverse and controllable volume average particle size, which can meet the diverse needs of back-end applications; (iii) has a glass transition temperature that can be controlled at 152-158°C, which can meet the use requirements in the application of back-end prepreg and carbon fiber reinforced composite material manufacturing processes and achieve a toughening effect. Although deionized water is used in the preparation process of the toughening agent of this application, the moisture content of the toughening agent product finally obtained can be controlled below 0.3%, and the impact on the back-end use can be ignored.

[0138] Table 2 further shows the performance test results of the prepregs prepared by physically dispersing the toughening agents described in Examples 1 to 10 and the powder materials of Comparative Example 1 with a resin matrix, impregnating the composite systems between carbon fiber layers, and undergoing coating, hot pressing, cooling, laminating, curling and other process steps. To ensure the comparability of the test results, in the sample preparation process, it has been ensured that except for the toughening agents used in each embodiment and the powder materials of Comparative Example, the other preparation processes and the raw materials used are the same.

[0139] Table 2 Performance test results of prepreg produced by toughening agent described in the embodiment and comparative powder material

[0140]

[0141] It can be seen from the performance test results of the prepregs produced using the toughening agents described in the examples and the comparative powder materials in Table 2 that the prepregs produced using the toughening agents of the present application have obvious advantages in post-impact compressive strength and type I fracture toughness, achieving unexpected results.

[0142] It can be seen that, compared with Comparative Example 1, the toughening agent of the present invention has achieved a breakthrough in material sphericity, particle size regulation, controllable glass transition temperature and prepreg performance produced in the back end.

[0143] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0144] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A toughening agent, characterized in that: The toughening agent is made of an oil phase mixture and a water phase mixture; The oil phase mixture includes thermoplastic plastics and organic solvents; the water phase mixture includes polyvinyl alcohol and deionized water; the thermoplastic plastics is polyamide, and the organic solvent is N-methyl-2-pyrrolidone; the preparation method of the toughening agent includes the following steps: 30.0 kg of N-methyl-2-pyrrolidone was weighed and placed in a container, heated to 30° C. and stirred until uniform; 2 kg of thermoplastic was added, stirred and dissolved to obtain a first dispersion system; nitrogen was filled into the container, and the gas in the container was replaced by 95-99% of nitrogen; 43 kg of a polyvinyl alcohol solution consisting of 3 kg of polyvinyl alcohol and 40 kg of deionized water was weighed and added dropwise to the first dispersion system at a rate of 0.3 kg / min, and stirred until the system presented a uniform milky white emulsion to obtain a second dispersion system; the second dispersion system was distilled at a vacuum degree of -0.09 MPa for 8 hours to remove the organic solvent, and the obtained slurry was washed with water, classified, and subjected to particle size classification, and rinsed and diluted with 65° C. hot water; the sieved intermediate was subjected to solid-liquid separation, drying, crushing and other treatments to obtain the toughening agent.

2. A toughening agent as claimed in claim 1, used in the manufacturing process of prepreg and carbon fiber reinforced composite materials.

Citation Information

Patent Citations

  • Production of spherical fine powder of polymer

    JP1989158042A

  • Polyamide fine particle, prepreg, and carbon fiber-reinforced composite material

    JP2009221460A